DISPOSABLE OR REUSABLE MASK? STUDENT PREFERENCE IN THE ERA OF COVID-19 PANDEMIC - Proverawati, Atikah; Najmudin; Saepuloh, Asep (The journal of contemporary issues in business and government, 2021)
Healthscience students havean understanding ofthe high effectiveness of disposable masks. Many masks on the market can change the choice of mask type for their daily needs. This qualitative research with a phenomenological approach was usedin-depth interviews. The research sample was six students in the Faculty of Health Sciences at the University of JenderalSoedirman. The results found some factors related to mask preference in health sciences students. Further research may be needed in production and marketing issues.